1991
DOI: 10.1021/bi00235a011
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence of tryptophan dipeptides: correlations with the rotamer model

Abstract: The multiexponential decay of tryptophan derivatives has previously been explained by the presence of rotamers having different fluorescence lifetimes, but it has been difficult to correlate rotamer structure and physical properties. New time-resolved and static data on dipeptides of the type Trp-X and X-Trp, where X is another aminoacyl residue, are consistent with the rotamer model and allow some correlations. That a dominant rotamer of Trp-X zwitterion has the -NH3+ group near the indole ring was inferred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
105
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(115 citation statements)
references
References 54 publications
9
105
1
Order By: Relevance
“…The three isotropic times were also interpreted as originating from different rotameric states from the tryptophan. 26 In our data, only one ns time was found. However, it is difficult to extract two ns isotropic times from our measurements, considering the restricted time range of the streak camera synchroscan unit (2.2 ns, although the "backsweep" enables us to estimate longer times).…”
Section: Discussioncontrasting
confidence: 50%
“…The three isotropic times were also interpreted as originating from different rotameric states from the tryptophan. 26 In our data, only one ns time was found. However, it is difficult to extract two ns isotropic times from our measurements, considering the restricted time range of the streak camera synchroscan unit (2.2 ns, although the "backsweep" enables us to estimate longer times).…”
Section: Discussioncontrasting
confidence: 50%
“…Because the distance between the Trp rings is 3.0 -3.5 Å, energy transfer is expected to make a significant contribution to the fluorescence quenching because this distance is shorter than the Förster distance for Trp-Trp FRET homotransfer (R 0 estimated at 4 -16 Å) (29). However, other mechanisms such as static quenching (30) are also likely to play a role.…”
Section: Discussionmentioning
confidence: 99%
“…Work on tryptophanyl dipeptides has been used very elegantly by Knutson and coworkers to investigate the multiexponential decay of tryptophan in light of the rotamer model [22][23]. In these time resolved studies, the authors studied the multiexponential fluorescence decay in the picosecond regime and concluded that it is associated to ground state heterogeneity that may arise from different conformational rotamers of the peptide side chains.…”
Section: Introductionmentioning
confidence: 99%